Economic evaluation of cleaning and disinfection of facilities from broiler chickens challenged with Campylobacter jejuni - de Castro Burbarelli, Maria Fernanda (2019)
For a new management practice to be adopted in broiler production, it must be efficient and economically viable. Few studies have been conducted with the purpose of evaluating costs and revenues relative to cleaning and disinfection. Based on the need to show economic efficiency of these practices, we compared two cleaning and disinfection protocols. The first method is more detailed and developed in seven steps, whereas the second method is more simplified with three steps. The costs, estimated total revenue from poultry carcass sale, and gross margin of sale were calculated for each cleaning and disinfection program. As expected, the cost of executing the first protocol was greater than the second one. However, due to the positive influences of preventive procedures, such as cleaning and disinfection on broiler performance, it was hypothesized that the two protocols would have similar gross margins from the sale of chicken carcasses. This study demonstrates an increase in economic viability when invested in a more detailed and complete cleaning and disinfection protocol. From the results obtained with the present study, it is possible to demonstrate a greater profitability and economic feasibility when a more detailed cleaning and disinfection protocol was carried out, due to similarity of its gross margin from the sale of product compared with simplified protocol.